2004
DOI: 10.1097/01.pgp.0000139711.22158.14
|View full text |Cite
|
Sign up to set email alerts
|

Loss of β-Catenin Is Associated With Poor Survival in Ovarian Carcinomas

Abstract: The catenins (alpha-, beta- and gamma-) are cytoplasmic proteins that bind to the conserved tail of the epithelial cadherin molecule. The function of epithelial cadherin at the adherens junctions is dependent on the catenins for efficient cell-to-cell adhesion. Loss of catenin expression has been reported in several human cancers and associated with poor tumor differentiation, advanced tumor stage, and poor patient survival. In this study, we investigated the clinical relevance of alpha-, beta-, and gamma-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
4
13
2
Order By: Relevance
“…There is much evidence that the canonical Wnt pathway does not likely play a role in epithelial ovarian cancer tumors that are not of endometrioid origin (14,27,28). Our results were consistent with this established observation.…”
Section: Discussionsupporting
confidence: 82%
“…There is much evidence that the canonical Wnt pathway does not likely play a role in epithelial ovarian cancer tumors that are not of endometrioid origin (14,27,28). Our results were consistent with this established observation.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike most previous reports [38][39][40][41] , which revealed only one or a few members of this complex were associated with patients' survival, our result demonstrated that all molecules of E-cadherin/catenin complex were significantly correlated with HCC patients' survival. However, when E-cadherin/catenin complex status and other clinicopathological parameters were analyzed by the Cox regression model, abnormal expression of the E-cadherin/catenin complex was not found to be an independent prognostic factor.…”
Section: Discussioncontrasting
confidence: 55%
“…18 This study's authors also stated that in early stage ovarian cancer, determination of the b-catenin expression pattern could prove to be useful in selecting low-risk patients, 18 although opposite reports have also been reported. [54][55][56] In our cohort, we found that patients exhibiting low membranous b-catenin expression had a poor outcome compared with those showing high membranous expression. In addition, patients showing nuclear staining were in an intermediate risk group.…”
Section: Discussionmentioning
confidence: 61%